2018
DOI: 10.1007/s12035-018-1151-4
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Biomarkers for Early Detection of Alzheimer’s and Parkinson’s Diseases

Abstract: Neurological disorders are found to be influencing the peripheral tissues outside CNS. Recent developments in biomarkers for CNS have emerged with various diagnostic and therapeutic shortcomings. The role of central biomarkers including CSF-based and molecular imaging-based probes are still unclear for early diagnosis of major neurological diseases. Current trends show that early detection of neurodegenerative diseases with non-invasive methods is a major focus of researchers, and the development of biomarkers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 154 publications
0
43
0
Order By: Relevance
“…Very few data are available on the blood levels of amyloid protein. Previous cross-sectional studies con rmed that plasma Aβ of AD patients is not much different from normal controls [55], but somewhat promising results have been seen for combinations of Aβ 1−42 and Aβ 1−40 . Of note, recent studies allowed us to measure very low amounts of several Aβ-related peptides in plasma using ultrasensitive assays, supporting the use of plasma Aβ42/40 ratios as surrogate biomarkers of cerebral Aβ deposition [56,57].…”
Section: Discussionmentioning
confidence: 97%
“…Very few data are available on the blood levels of amyloid protein. Previous cross-sectional studies con rmed that plasma Aβ of AD patients is not much different from normal controls [55], but somewhat promising results have been seen for combinations of Aβ 1−42 and Aβ 1−40 . Of note, recent studies allowed us to measure very low amounts of several Aβ-related peptides in plasma using ultrasensitive assays, supporting the use of plasma Aβ42/40 ratios as surrogate biomarkers of cerebral Aβ deposition [56,57].…”
Section: Discussionmentioning
confidence: 97%
“…15 It becomes toxic as a result of intraneuronal accumulation due to an impaired proteasomal degradation by ubiquitin-C-terminal hydrolase-L1 and β-glucocerebrosidase, 25,38,39 followed by aggregation, misfolding, and phosphorylation at serine-129. 40 Although toxic α-synuclein affects all neurons, it appears to provide a semi-specific effect on nigrostriatal dopaminergic neurons, probably enhancing the cytosolic dopamine autotoxicity. 11,41 Tau proteinopathy, like α-synucleinopathy, promotes neurodegeneration due to impaired axonal transport in affected neurons, including nigrostriatal dopaminergic neurons.…”
Section: Pathogenesismentioning
confidence: 99%
“…It was shown that the concentration of total α-synuclein decreased in CSF and plasma in PD patients, whereas the concentrations of toxic phosphorylated at serine-129 and oligomeric α-synuclein increased in both BF compared to age-matched control. 19,40,[75][76][77][78] The sensitivity and specificity of the PD diagnosis increase up to 89.3% and 90.6%, when assessing the ratio of α-synuclein oligomers to the total content of α-synuclein. 13,21,75 Aggregated and phosphorylated tau protein is also considered as a biomarker, since their concentrations decrease in CSF in PD patients.…”
Section: Targeted Search For Biomarkers In Body Fluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies about salivary biomarkers in patients with AD have been conducted; but to the best of our knowledge, few studies have been performed on salivary cholinesterase enzyme changes and the benefits of saliva in AD. Therefore, the aim of this study is to compare salivary AChE and PChE in patients with AD and in healthy control groups.…”
Section: Introductionmentioning
confidence: 99%